Numerical study of the effect of stenosis on the hemodynamics of a popliteal artery - Liuliu Shi; Xinru Xiang; Jinlong Liu; Wei Zhu (AIP Advances)
The investigation of flow characteristics within the popliteal artery is fundamental to understanding the progression of lower limb arterial disease, given its high susceptibility to atherosclerosis and its frequent manifestation of stenosis. Research on the hemodynamics associated with popliteal artery stenosis remains limited, particularly in cardiovascular diseases. This study comprehensively examines how Newtonian and non-Newtonian fluid models influence the hemodynamic simulations of popliteal artery stenosis. Key hemodynamic parameters, such as velocity, time-averaged wall shear stress (TAWSS), oscillatory shear index (OSI), and relative residence time (RRT), were systematically examined through numerical simulations to assess their influence and variability in arteries exhibiting different degrees of stenosis compared to healthy arteries. The findings indicate that both models’ velocity and wall shear stress (WSS) distributions are largely comparable during the systolic phase (0.04–0.07 s), characterized by elevated velocities. However, during the countercurrent diastolic phase (0.21–0.40 s), the viscosity of the non-Newtonian fluid model experiences an increase, leading to reduced velocity distributions relative to the Newtonian fluid model. In particular, a 12% disparity in velocities is observed between the two models, indicating that the non-Newtonian model is better suited for comprehensive hemodynamic analysis in simulations involving stenotic popliteal arteries. Furthermore, a distinct flow separation occurs at the stenosis site, with blood flow velocity and WSS exhibiting significant increases as the stenosis severity escalates. For instances where hemodynamic parameters demonstrate minimal variations at stenosis levels below 60%, OSI and RRT are elevated. In contrast, TAWSS remains low, potentially fostering plaque formation. In contrast, when hemodynamic parameters undergo substantial changes at stenosis levels exceeding 60%, TAWSS rises, which may facilitate plaque rupture. This simulation provides a comprehensive analysis of hemodynamic parameter variations across different degrees of stenosis, offering clinicians a valuable instrument for enhancing their understanding of the pathogenic mechanisms associated with popliteal artery atherosclerosis and stenosis.